Implementation Model Of Integrated Islamic Education Curriculum Based On Tauhidik: Case Study At Sd Abata Islamic School Karawang - Muhajir, Ahmad; Amirudin, Amirudin; Arifudin, Yadi Fahmi (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2026)
This study aims to describe the implementation model of an integrated Islamic Religious Education (IRE) curriculum at SD Abata Islamic School Karawang. The background of this study is the need to strengthen the synergy between IRE learning and general subjects and Islamic values to support student character development. The research method used a qualitative case study approach with the main techniques of participatory observation, in-depth interviews, and document analysis, involving a total of 15 informants consisting of the principal, IRE teachers, classroom teachers, curriculum coordinators, students, and parents. The results showed that the PAI curriculum integration model comprised three main components: (1) the development of learning themes that linked PAI competencies with cross-subject competencies; (2) collaboration among teachers in designing contextual and Islamic-based learning; and (3) evaluation that covered cognitive, affective, and spiritual aspects. This implementation model was carried out consistently for one semester based on a cycle of planning, implementation, and evaluation. As a result, the application of the integrated curriculum model was proven to improve students' understanding of religious values, strengthen attitudes of tolerance and discipline, and support the achievement of more holistic learning outcomes. This study recommends that schools adopt this model as a framework for developing an integrated PAI curriculum and provide ongoing training for teachers to optimize its implementation.